The role of forensic accounting in reducing financial fraud practices (Zien Journal of Social Sciences and Humanities, 2022)
The aim of the research is to clarify the role and importance of forensic accounting in reducing financial fraud practices and the need for companies and economic units to forensic accounting. The research concluded that forensic accounting is an important matter for the regulatory organizations responsible for detecting fraud and corruption of a financial nature, and forensic accounting is the best way in the hands of the regulatory authorities to reduce financial fraud practices, and therefore it is necessary to provide legal legislation that defines the duties of the forensic accountant in both courts and financial and supervisory institutions . As well as developing and training forensic accountants so that they have the ability and knowledge of fraudulent practices and methods and how to detect it